2014
DOI: 10.1007/s10943-014-9935-y
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability Analysis of the ‘SayangKU’ (MyLove) in Intervention for Addressing Adolescents Involved in Free Sex

Abstract: A module entitled 'SayangKU' (MyLove), based on the Islamic perspective, was developed as an instrument to assist adolescents that involved in premarital sexual activity. The module comprises four phases: Love of God (Allah), Love of the Prophet, Love of Oneself, and Love of the Ummah (world). From analysis of Rasch, the value of item reliability was .80 and an individual reliability was .95. Dimensionality value was more than 40 % variance explained by measures, and level of agreement among experts was 86.88 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Scores found from this measure designated the participants' view once confronting problems of perception of Malaysian morals and cultural values Ghani et al, 2014). Example instrument questions comprised declarations like "Understanding jokes and humors" etc.…”
Section: Socio Cultural Adaptation Scalementioning
confidence: 99%
“…Scores found from this measure designated the participants' view once confronting problems of perception of Malaysian morals and cultural values Ghani et al, 2014). Example instrument questions comprised declarations like "Understanding jokes and humors" etc.…”
Section: Socio Cultural Adaptation Scalementioning
confidence: 99%
“…The whole perspective transformation process took more than 10 years as the respondents faced the relapse problem. Due to lack of confidence and exposure respondents experienced a long time for the perspective transformation process [24,25,26]. Perspective transformation process for the former drug addicts is holistic, unique process and different from other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Dick et al (2015) believe that data analysis procedures in the expert evaluation phase should be straightforward and the data should be summarized within the study questions for easy interpretation, including frequency counts. Therefore, many researchers in the field of education both locally and internationally use this method to validate the content of their modules such as in teen sexual education, mathematics education and counselling education of drug addicts (Ghani et al, 2015;Setambah et al, 2017;Mohd Noah & Ahmad, 2005). One method that is often practiced by the researchers in assessing content validity is based on the method proposed by Lynn (El-Den et al, 2018;Kadar et al, 2018;Polit & Beck, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that the percentage value of a module that has been assessed by experts should be calculated. According to Mohd Noah & Ahmad (2005) and Ghani et al (2015), content validity percentage can be calculated using the formula as below:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation